STUDY ON MECHANICAL BEHAVIOR OF VOID UNDER THE INTERNAL PRESSURE AND EXTERNAL LOAD IN STEEL - FAN JunKai; HOU GaoJie (Jixie qiangdu)
The existence of hydrogen in steel can lead to the decline of its mechanical properties,and result in high hydrogen pressure within void in steel. In the past, the research on the void of steel parts mostly focused on the effect of external load. The study of the mechanical properties of void under external load and internal pressure is rarely involved. Based on the hydrogen pressure theory and the gas state equation, a finite element model of void under external load and internal pressure is established. The effects of hydrogen pressure and void shape on the stress field and deformation behavior of the voids were investigated. The results show the hydrogen pressure in the void has a strong hindrance to the deformation of the void. Spherical voids are the most prone to crack initiation. The ellipsoidal void with an angle of 30 ° from the loading direction is most likely to generate cracks at the tangent point of the inner surface and the plane in the vertical load-carrying direction. The stress concentration is due to the presence of hydrogen inside void in the steel parts.And it severely reduces the strength of the parts.